Graphene reinforced copper composite slurry, preparation method and application thereof
Patent Information
- Application Number
- CN202611174431.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]本申请提供了一种石墨烯增强铜复合浆料及其制备方法与应用,旨在解决银基导电浆料成本高而现有铜基导电浆料易氧化,以及石墨烯易分散不均、与铜粉界面结合力弱的技术问题
[0009]上述石墨烯增强铜复合浆料及其制备方法与应用,通过选取特定层数和尺寸的石墨烯,兼顾了石墨烯的分散稳定性和导电增强效果,避免层数过少易团聚、层数过多导电性增强效果有限的问题;通过对铜粉进行表面改性处理,使石墨烯与铜粉之间由物理附着转变为有效的化学键合,显著增强界面结合力,降低了体积电阻率并提升了石墨烯包覆保护效果的持久性。所得浆料兼具高导电性、稳定性和成本优势,可替代银浆广泛应用于柔性印刷电子领域。
Smart Images

Figure CN122907439A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of conductive materials technology, and in particular to graphene-reinforced copper composite paste, its preparation method and application. Background Technology
[0002] With the rapid development of the Internet of Things and the flexible printed electronics industry, the market demand for low-cost flexible conductive pastes continues to grow. Currently, the mainstream product is silver-based conductive paste, but its raw material costs are high and resources are scarce, making it difficult to meet the needs of large-scale industrial applications.
[0003] Copper possesses excellent conductivity similar to silver but is inexpensive, making it an ideal alternative. However, copper powder readily oxidizes in air, forming an insulating oxide layer that rapidly degrades its conductivity. Furthermore, the sintering temperature of traditional copper-based pastes is typically above 200°C, incompatible with the upper temperature limits of commonly used flexible substrates such as PET and PEN, thus restricting their application in flexible printed electronics. Graphene exhibits excellent conductivity, chemical stability, and sheet-like coating properties; combining it with copper powder can mitigate copper oxidation and construct a highly efficient conductive network. However, existing graphene-copper composite technologies still have significant shortcomings: improper selection of the number and size of graphene layers can lead to agglomeration, uneven dispersion, or poor conductive network construction; the lack of effective chemical bonding between graphene and copper powder results in weak interfacial adhesion, making them prone to detachment during grinding and printing processes, leading to increased interfacial resistance and reduced coating protection. Summary of the Invention
[0004] This application provides a graphene-reinforced copper composite paste, its preparation method, and its application, aiming to solve the technical problems of high cost of silver-based conductive pastes, easy oxidation of existing copper-based conductive pastes, uneven dispersion of graphene, and weak interfacial bonding between graphene and copper powder. By selecting graphene with a specific number and size of layers and modifying the surface of copper powder, the interfacial bonding between graphene and copper powder is enhanced, resulting in a graphene-reinforced copper composite paste with both excellent conductivity and oxidation resistance.
[0005] In a first aspect, embodiments of this application provide a method for preparing a graphene-reinforced copper composite slurry. The method includes: S1: Preparing a graphene dispersion: dispersing graphene with 10-15 layers and a lateral dimension of 400-600 nm in a solvent, adding a dispersant, and ultrasonically treating to obtain a graphene dispersion with a graphene concentration of 0.5-5 g / L; S2: Preparing surface-modified copper powder: immersing copper powder in a solution containing a surface modifier and treating for 10-60 minutes to obtain surface-modified copper powder; S3: Composite dispersion: adding the surface-modified copper powder obtained in step S2 to the graphene dispersion obtained in step S1, stirring and ultrasonically treating to adsorb graphene onto the surface of the copper powder, obtaining graphene-coated copper powder composite particles; S4: Slurry preparation: mixing the graphene-coated copper powder composite particles obtained in step S3 with an organic carrier and grinding to obtain a graphene-reinforced copper composite slurry.
[0006] Secondly, embodiments of this application provide a graphene-reinforced copper composite slurry. The graphene-reinforced copper composite slurry is prepared by the method described in the first aspect above; the slurry contains 0.5wt%-5wt% graphene and 60wt%-85wt% copper powder; after sintering at 150°C-200°C under nitrogen protection for 30-60 minutes, the slurry has a volume resistivity of 3-10 μΩ·cm.
[0007] Thirdly, embodiments of this application provide the application of graphene-reinforced copper composite paste in flexible printed circuits, RFID tags, membrane switches, electromagnetic shielding films, or heating films.
[0008] Fourthly, embodiments of this application provide a method for preparing a flexible printed circuit based on the above-mentioned graphene-reinforced copper composite paste. The method includes the following steps: S10: depositing the graphene-reinforced copper composite paste obtained in the second aspect onto a flexible substrate by screen printing, inkjet printing, or gravure printing to form a conductive pattern; S11: sintering at 150°C-200°C under nitrogen or vacuum conditions for 30-60 minutes.
[0009] The aforementioned graphene-reinforced copper composite paste, its preparation method, and its application balance the dispersion stability and conductivity enhancement effects of graphene by selecting graphene with specific numbers and sizes, avoiding the problems of easy agglomeration when the number of layers is too small and limited conductivity enhancement when the number of layers is too large. Surface modification of the copper powder transforms the physical adhesion between graphene and copper powder into effective chemical bonding, significantly enhancing interfacial bonding, reducing volume resistivity, and improving the durability of the graphene coating protection effect. The resulting paste combines high conductivity, stability, and cost advantages, and can replace silver paste for widespread application in flexible printed electronics. Attached Figure Description
[0010] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0011] Figure 1 A flowchart illustrating the preparation method of the graphene-reinforced copper composite slurry provided in the embodiments of this application.
[0012] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0013] The following embodiments are provided to better understand this application and are not limited to the preferred embodiments described herein. They do not constitute a limitation on the content and scope of protection of this application. Any product that is the same as or similar to this application, derived by anyone under the guidance of this application or by combining features of this application with other prior art, falls within the scope of protection of this application.
[0014] Unless otherwise stated or in case of contradiction, the terms or phrases used herein shall have the following meanings: In this application, the selection scope involving "and / or" includes any one of two or more related listed items, as well as any and all combinations of the related listed items. For example, "A and / or B" includes three parallel options: A, B, and A+B.
[0015] In this application, the terms "multiple" or "various" are used unless otherwise specified, referring to a quantity greater than or equal to 2. For example, "one or more" means one or more types.
[0016] In this application, terms such as "further," "even more," and "particularly" are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of this application.
[0017] In this application, the terms "optionally," "optionally," and "optional" refer to options that are optional, meaning they can be selected from either "with" or "without." If multiple "optional" options appear in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "optional" option is independent.
[0018] In this application, the terms "first aspect," "second aspect," "third aspect," and "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," and "fourth," etc., serve only a non-exhaustive enumeration purpose and should be understood not to constitute a closed limitation on quantity.
[0019] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0020] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0021] Please refer to Figure 1 This is a flowchart illustrating the preparation method of graphene-reinforced copper composite slurry provided in the embodiments of this application. This application provides a method for preparing graphene-reinforced copper composite slurry, the method comprising steps S1-S4.
[0022] Step S1: Prepare graphene dispersion. Graphene with 10-15 layers and a lateral dimension of 400-600 nm is dispersed in a solvent, a dispersant is added, and the mixture is ultrasonically treated to obtain a graphene dispersion with a graphene concentration of 0.5-5 g / L. In step S1, the graphene preferably has a lateral dimension of 500 nm. The dispersant is selected from one or more of polyvinylpyrrolidone (PVP), sodium dodecylbenzene sulfonate (SDBS), and polyvinyl alcohol (PVA), and its amount is 50%-200% of the graphene mass. The solvent is selected from one or more of deionized water, ethanol, isopropanol, and N-methylpyrrolidone (NMP). 10-15 layers of graphene can achieve both uniform dispersion and enhanced conductivity, balancing conductivity and dispersibility. Graphene with a lateral dimension of 400-600 nm is chosen to match the particle size of the copper powder, enabling the formation of effective conductive pathways between copper powder particles without easily breaking.
[0023] Step S2: Prepare surface-modified copper powder. Immerse copper powder in a solution containing a surface modifier and treat for 10-60 minutes to obtain surface-modified copper powder; In step S2, the copper powder has a particle size of 1-20 μm, preferably a mixed particle size of 5-15 μm, wherein 5 μm copper powder accounts for 30-50% and 15 μm copper powder accounts for 50-70%. The concentration of the surface modifier solution is 0.1-2 g / L, and the surface modifier is selected from one of γ-aminopropyltriethoxysilane (KH-550) and benzotriazole (BTA), or both γ-aminopropyltriethoxysilane and benzotriazole. Modifying the surface of copper powder with a surface modifier can enhance the interfacial bonding force between graphene and copper powder and reduce the interfacial resistance.
[0024] Step S3, Composite Dispersion. The surface-modified copper powder obtained in step S2 is added to the graphene dispersion obtained in step S1, stirred and ultrasonically treated to allow graphene to be adsorbed onto the surface of the copper powder, resulting in graphene-coated copper powder composite particles; In step S3, the mass ratio of graphene to copper powder is 0.5:99.5-5:95, preferably 1:99 to 3:97. Further, in step S3, after the graphene is adsorbed onto the surface of the copper powder, a silver layer is formed by in-situ reduction of the graphene-coated copper powder surface, resulting in Cu@Gr@Ag core-shell structured composite conductive particles. The silver layer formed by the silver nanoparticles can lower the sintering temperature and improve conductivity.
[0025] Step S4, slurry preparation. The graphene-coated copper powder composite particles obtained in step S3 are mixed with an organic carrier and ground to obtain a graphene-reinforced copper composite slurry.
[0026] In step S4, the organic carrier comprises resin, solvent, additives, and dispersant, wherein the resin accounts for 10-30% of the total mass of the organic carrier, the solvent accounts for 60-85%, the additives account for 1-5%, and the dispersant accounts for 1-10%. The resin is selected from thermosetting resins, including epoxy resin, phenolic resin, and acrylic resin, and the solvent is selected from one or more of terpineol, butyl carbitol, diethylene glycol butyl ether, and ethylene glycol ethyl ether acetate.
[0027] Preferably, after obtaining the graphene-reinforced copper composite slurry in step S4, an antioxidant enhancement treatment is further included. An antioxidant is added to the graphene-reinforced copper composite slurry. The antioxidant is selected from one or more of benzimidazole, thiourea, and ascorbic acid, and the amount added is 0.1-1% of the total mass of the graphene-reinforced copper composite slurry. Based on the physical coating of copper powder with graphene, the further addition of an antioxidant for chemical protection can significantly improve the long-term stability of the slurry.
[0028] This application also provides a graphene-reinforced copper composite slurry, which is prepared by the above-described method. The slurry contains 0.5wt%-5wt% graphene and 60wt%-85wt% copper powder. After sintering at 150℃-200℃ under nitrogen protection for 30-60 minutes, the slurry exhibits a volume resistivity of 3-10 μΩ·cm, and after being exposed to air for 60 days, the change in volume resistivity is less than 15%.
[0029] This application also provides a method for preparing a flexible printed circuit based on the above-mentioned graphene-reinforced copper composite paste, the preparation method including steps S10-S11.
[0030] Step S10: The above-mentioned graphene-reinforced copper composite paste is deposited on a flexible substrate by screen printing, inkjet printing or gravure printing to form a conductive pattern.
[0031] In step S10, the flexible substrate is selected from polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), and polycarbonate (PC), with a thickness of 25-188 μm. The conductive pattern has a linewidth of 20-500 μm, a thickness of 5-50 μm, and a sheet resistance of 10-100 mΩ / sq.
[0032] Step S11: Sinter at 150℃-200℃ under nitrogen or vacuum conditions for 30-60 minutes.
[0033] After sintering in step S11, a protective layer can also be coated on the surface of the conductive pattern.
[0034] The following will illustrate how to prepare graphene-reinforced copper composite paste using different embodiments, and how to prepare graphene-reinforced copper composite paste containing nano-silver based on this.
[0035] Example 1 This embodiment provides a method for preparing graphene-reinforced copper composite slurry, including the following steps: (1) Preparation of graphene dispersion 2g of graphene with 10-15 layers and a lateral dimension of 500nm was dispersed in 400mL of deionized water. 2g of polyvinylpyrrolidone (PVP) of specification K30 was added, and the mixture was sonicated for 2 hours to obtain a graphene dispersion with a graphene concentration of 5g / L. The sonication parameters were set as follows: power 500W, frequency 40kHz.
[0036] (2) Preparation of surface-modified copper powder Take 40g of copper powder with a particle size of 5μm and 60g of copper powder with a particle size of 15μm to obtain 100g of copper powder with mixed particle sizes. Dissolve 1g of γ-aminopropyltriethoxysilane (KH-550) in 500mL of ethanol to prepare an ethanol solution containing the surface modifier KH-550. Immerse the 100g of copper powder with the above mixed particle sizes into the ethanol solution containing the surface modifier KH-550, stir at room temperature for 30 minutes, filter, wash with ethanol, and dry in vacuum at 60°C to obtain surface-modified copper powder.
[0037] (3) Composite dispersion The surface-modified copper powder obtained in step (2) was added to the graphene dispersion obtained in step (1), and mechanically stirred at 500 rpm for 1 hour. Then, it was ultrasonically treated at 300 W for 30 minutes to allow the graphene to be uniformly adsorbed onto the surface of the copper powder. After filtration, it was dried in a vacuum at 60°C to obtain graphene-coated copper powder composite particles.
[0038] (4) Slurry preparation 20g of epoxy resin (E-44), 65g of terpineol, 10g of butyl carbitol, and 5g of BYK-110 dispersant were mixed and stirred at 60°C for 2 hours to obtain an organic carrier. 75g of the graphene-coated copper powder composite particles obtained in step (3) were mixed with 25g of the organic carrier and ground three times with a three-roll mill, with roller gaps of 50μm, 25μm, and 10μm respectively, to obtain a graphene-reinforced copper composite slurry.
[0039] The performance of the graphene-reinforced copper composite slurry prepared in this embodiment was tested, and the results are as follows: The graphene content is 2 wt%, and the copper powder content is 75 wt%; at 25°C and a shear rate of 10 s... -1 The viscosity of the slurry was measured to be 18 Pa·s under the specified conditions, and the fineness of the slurry was ≤10 μm as measured by the scraper fineness meter method. It exhibited good printability, with clear lines and neat edges after printing with a 200-mesh screen. After sintering at 180°C under nitrogen protection for 40 minutes, the volume resistivity was measured to be 6.8 μΩ·cm using the four-probe method. The adhesion to the PET substrate reached grade 5B (measured according to the ASTM D3359 cross-cut test). After being exposed to air for 60 days, the volume resistivity changed by 12%.
[0040] Example 2 This embodiment provides a method for preparing a graphene-reinforced copper composite slurry containing nano-silver. Except for step (3), the other steps are the same, including the following steps: (1) Preparation of graphene dispersion 2g of graphene with 10-15 layers and a lateral dimension of 500nm was dispersed in 400mL of deionized water. 2g of polyvinylpyrrolidone (PVP) of specification K30 was added, and the mixture was sonicated for 2 hours to obtain a graphene dispersion with a graphene concentration of 5g / L. The sonication parameters were set as follows: power 500W, frequency 40kHz.
[0041] (2) Preparation of surface-modified copper powder Take 40g of copper powder with a particle size of 5μm and 60g of copper powder with a particle size of 15μm to obtain 100g of copper powder with mixed particle sizes. Dissolve 1g of γ-aminopropyltriethoxysilane (KH-550) in 500mL of ethanol to prepare an ethanol solution containing the surface modifier KH-550. Immerse the 100g of copper powder with the above mixed particle sizes into the ethanol solution containing the surface modifier KH-550, stir at room temperature for 30 minutes, filter, wash with ethanol, and dry in vacuum at 60°C to obtain surface-modified copper powder.
[0042] (3) Composite dispersion The surface-modified copper powder obtained in step (2) was added to the graphene dispersion obtained in step (1), and mechanically stirred at 500 rpm for 1 hour. Then, it was ultrasonically treated at 300 W for 30 minutes to ensure that the graphene was uniformly adsorbed onto the surface of the copper powder. Next, a silver nanoparticle layer was formed on the graphene-coated copper powder surface using an in-situ reduction method. The mixture was filtered and dried in a vacuum at 60°C to obtain Cu@Gr@Ag core-shell composite particles. In this embodiment, the silver nanoparticles generated by the in-situ reduction method form a continuous and dense silver layer on the surface of the graphene-coated copper powder, resulting in Cu@Gr@Ag core-shell composite particles comprising a copper core, a graphene intermediate layer, and a silver outer shell. More specifically, in this embodiment, a silver precursor is added to the graphene dispersion and an in-situ reduction method is used to form a silver layer composed of silver nanoparticles on the surface of the graphene-coated copper powder.
[0043] (4) Slurry preparation 20g of epoxy resin (E-44), 65g of terpineol, 10g of butyl carbitol, and 5g of BYK-110 dispersant were mixed and stirred at 60°C for 2 hours to obtain an organic carrier. 75g of the Cu@Gr@Ag core-shell composite particles obtained in step (3) were mixed with 25g of the organic carrier and ground three times with a three-roll mill, with roller gaps of 50μm, 25μm, and 10μm respectively, to obtain a graphene-reinforced copper composite slurry containing nano-silver.
[0044] The performance of the slurry obtained in this embodiment was tested, and the test results are as follows: After sintering at 150°C under nitrogen protection for 30 minutes, the volume resistivity measured by the four-probe method was 4.5 μΩ·cm; the adhesion to the PET substrate reached grade 5B (measured according to the ASTM D3359 cross-cut test); in the bending test, the resistance change rate was 18% after bending radius of 3 mm and 10,000 bending cycles.
[0045] Example 3 This embodiment provides an application of graphene-reinforced copper composite paste in flexible heating films.
[0046] Using the graphene-reinforced copper composite paste prepared in Example 1, a serpentine heating pattern was formed on a 125 μm thick PET substrate by screen printing. The conductive pattern had a linewidth of 200 μm and a thickness of 20 μm. After sintering the printed PET substrate at 180°C under nitrogen protection for 40 minutes, a 12V DC voltage was applied. The resulting heating film achieved a power density of 800 W / m² and a surface temperature uniformity of ±3°C.
[0047] The graphene-reinforced copper composite slurry prepared in Example 1 and the slurries prepared in Comparative Examples 1-3 were sintered under the same conditions, and their properties were compared and analyzed. The results are shown in Table 1. Table 1 Comparison of conductivity and long-term stability Table 1 shows that the volume resistivity reflects the conductivity of the slurry, and the oxidation resistance reflects the long-term stability of the slurry. The results show that the graphene-reinforced copper composite slurry of Example 1 has better conductivity and long-term stability than the slurries of Comparative Examples 1-3.
[0048] Comparative Example 1 The slurry was prepared according to the method of Example 1, except that in step (1) of this comparative example, single-layer graphene with a lateral size of 1-5 μm was dispersed in a solvent, a dispersant was added, and the mixture was ultrasonically treated to obtain a graphene dispersion. The remaining steps were the same as in Example 1. During the preparation process, the graphene dispersion showed significant sedimentation after standing for 2 hours, indicating that the single-layer graphene was prone to agglomeration and could not form a stable dispersion. The resulting slurry had poor printing performance and rough line edges, indicating that the viscosity of the prepared graphene-reinforced copper composite slurry was uneven, resulting in a decrease in the resolution of the printed conductive pattern. After sintering the slurry under the same conditions as in Example 1 (180°C, nitrogen protection, sintering for 40 minutes), the volume resistivity measured by the four-probe method was 15 μΩ·cm, which was significantly higher than 6.8 μΩ·cm in Example 1. This indicates that the improper selection of the number and size of graphene layers made it difficult to form an effective conductive path, and the conductivity of the prepared slurry was worse than that of Example 1.
[0049] Comparative Example 2 The slurry was prepared according to the method of Example 1, except that step (2) of the copper powder surface modification treatment was omitted in this comparative example, while the remaining steps were the same as in Example 1. After sintering under the same conditions as in Example 1 (180°C, nitrogen protection, sintering for 40 minutes), the volume resistivity of the slurry measured by the four-probe method was 12 μΩ·cm, which was higher than 6.8 μΩ·cm in Example 1. The conductivity of the prepared slurry was worse than that of Example 1, indicating that the lack of copper powder surface modification treatment resulted in weak interfacial bonding between graphene and copper powder and high interfacial resistance. After being placed in air for 60 days, the volume resistivity change rate was 35%, which was significantly higher than 12% in Example 1. The conductivity was even worse, and the long-term stability was also worse than that of Example 1, indicating that graphene gradually detached from the surface of copper powder during long-term placement, leading to gradual oxidation of copper powder.
[0050] Comparative Example 3 The slurry was prepared according to the method in Example 1, except that this comparative example prepared a pure copper slurry without using graphene; the slurry was prepared directly from pure copper powder, and the remaining steps were the same as in Example 1. After sintering under the same conditions as in Example 1 (180°C, nitrogen protection, sintering for 40 minutes), the volume resistivity of the resulting slurry, measured using the four-probe method, was 25 μΩ·cm, significantly higher than the 6.8 μΩ·cm of Example 1. The conductivity of the prepared pure copper slurry was significantly worse than that of Example 1, indicating that the conductive path formed solely by copper powder particles had high resistance, and the lack of graphene to improve conductivity was a significant drawback. After being exposed to air for 30 days, the copper powder was completely oxidized, and the slurry became ineffective and unable to conduct electricity, indicating that copper powder is easily oxidized when directly exposed to air, and the lack of physical coating by graphene slows down the oxidation rate of copper.
[0051] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing a graphene-reinforced copper composite slurry, characterized in that, The preparation method of the graphene-reinforced copper composite slurry includes: S1: Preparation of graphene dispersion: Graphene with 10-15 layers and a lateral size of 400-600 nm is dispersed in a solvent, a dispersant is added, and the dispersion is obtained by ultrasonic treatment. The graphene concentration is 0.5-5 g / L. S2: Preparation of surface-modified copper powder: Immerse copper powder in a solution containing a surface modifier and treat for 10-60 minutes to obtain surface-modified copper powder; S3: Composite dispersion: The surface-modified copper powder obtained in step S2 is added to the graphene dispersion obtained in step S1, stirred and ultrasonically treated to allow graphene to be adsorbed onto the surface of the copper powder, thus obtaining graphene-coated copper powder composite particles. S4: Slurry preparation: The graphene-coated copper powder composite particles obtained in step S3 are mixed with an organic carrier and ground to obtain a graphene-reinforced copper composite slurry.
2. The method for preparing the graphene-reinforced copper composite slurry as described in claim 1, characterized in that, In step S1, the dispersant is selected from one or more of polyvinylpyrrolidone, sodium dodecylbenzenesulfonate, and polyvinyl alcohol, and the amount used is 50%-200% of the graphene mass; the solvent is selected from one or more of deionized water, ethanol, isopropanol, and N-methylpyrrolidone.
3. The method for preparing the graphene-reinforced copper composite slurry as described in claim 1, characterized in that, In step S2, the copper powder has a particle size of 1-20 μm, the surface modifier solution concentration is 0.1-2 g / L, and the surface modifier is one of γ-aminopropyltriethoxysilane and benzotriazole, or γ-aminopropyltriethoxysilane and benzotriazole.
4. The method for preparing the graphene-reinforced copper composite slurry as described in claim 1, characterized in that, In step S3, the mass ratio of graphene to copper powder is 0.5:99.5-5:
95.
5. The method for preparing the graphene-reinforced copper composite slurry as described in claim 1, characterized in that, Step S3 also includes generating a silver layer by in-situ reduction of graphene onto the copper powder surface after graphene is adsorbed onto the copper powder surface, thus obtaining Cu@Gr@Ag core-shell structured composite conductive particles.
6. The method for preparing the graphene-reinforced copper composite slurry as described in claim 1, characterized in that, In step S4, the organic carrier comprises, by mass percentage, 10%-30% resin, 60%-85% solvent, 0%-5% additives and 1%-10% dispersant; the resin is selected from epoxy resin, phenolic resin and acrylic resin, and the solvent is selected from one or more of terpineol, butyl carbitol, diethylene glycol butyl ether and ethylene glycol ethyl ether acetate.
7. A graphene-reinforced copper composite paste, characterized in that, The slurry is prepared by any one of claims 1 to 6; the content of graphene in the slurry is 0.5wt%-5wt%, and the content of copper powder is 60wt%-85wt%; after the slurry is sintered at 150℃-200℃ under nitrogen protection for 30-60 minutes, the volume resistivity is 3-10μΩ·cm.
8. The application of the graphene-reinforced copper composite paste according to claim 7 in flexible printed circuits, RFID tags, membrane switches, electromagnetic shielding films, or heating films.
9. A method for preparing a flexible printed circuit based on the graphene-reinforced copper composite paste as described in claim 7, characterized in that, The preparation method includes: S10: The graphene-reinforced copper composite paste as described in claim 7 is deposited on a flexible substrate by screen printing, inkjet printing or gravure printing to form a conductive pattern. S11: Sinter at 150℃-200℃ under nitrogen or vacuum conditions for 30-60 minutes.
10. The method for fabricating a flexible printed circuit as described in claim 9, characterized in that, The flexible substrate is selected from polyethylene terephthalate, polyethylene naphthalate, polyimide, and polycarbonate, with a thickness of 25-188 μm; the conductive pattern has a line width of 20-500 μm, a thickness of 5-50 μm, and a sheet resistance of 10-100 mΩ / sq.